Debunking the Myth of Wool Allergy: Reviewing the Evidence for Immune and Non-immune Cutaneous Reactions - Michaela Zallmann; Pete K. Smith; Mimi L.K. Tang; Lynda J. Spelman; Jennifer L. Cahill; Gabriele Wortmann; Constance H. Katelaris; Katrina J. Allen; John C. Su (Medical Journals Sweden, 2017)
Although wool is commonly believed to cause irritant (non-immune) and hypersensitivity (immune) cutaneous reactions, the evidence basis for this belief and its validity for modern garments have not been critically examined. Publications from the last 100 years, using MEDLINE and Google Scholar, were analysed for evidence that wool causes cutaneous reactions, both immune-mediated (atopic dermatitis exacerbation, contact urticaria, allergic contact dermatitis) and non-immune-mediated (irritant contact dermatitis, itch). Secondary aims of this paper were to examine evidence that lanolin and textile-processing additives (formaldehyde, chromium) cause cutaneous reactions in the context of modern wool-processing techniques. Current evidence does not suggest that wool-fibre is a cutaneous allergen. Furthermore, contact allergy from lanolin, chromium and formaldehyde is highly unlikely with modern wool garments. Cutaneous irritation from wool relates to high fibre diameters (≥ 30-32 µm). Superfine and ultrafine Merino wool do not activate sufficient c-fibres to cause itch, are well tolerated and may benefit eczema management.